PENGEMBANGAN PERANGKAT PEMBELAJARAN ENGINETUNE UP TOYOTA MENGACU PADA PROBLEM BASED INSTRUCTION BERBASIS OTENTIK - Ulum, M. Arif Zainul; Samani, Muchlas; M. Cholik, M. Cholik (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
AbstractThis study aims to develop learning tool Engine tune up Toyota referring to problem based instruction based on authentic, which was applied in class X Mechanical Light Vehicle 2nd semester in SMK N Kare, Madiun.This study was conducted into five steps, they were analysis, planning, design, development and implementation based on model of the development cycle by Fenrich (1997). The data resultswere obtained as follows: validation of achievement test consist of LP1, LP2, and LP3. The score of correlation probability r (analysis) bigger than r (table).So it can be concluded the results were valid; The implementation of lesson plan with an average score of 4.6 as good category; students? activities in learning activities have reliability 94,33%; In analysing questions, there were easy and difficult category of questions. The cognitive?s achievement in pretest was 0%, while in posttest was 100%; Psychomotoric?s achievement shows that the average score of students RPP 1 (91,1), RPP 2 (91,2), RPP 3(91). All of the students have mastered the outcome learning.; the average score of students? behavioral in affective?s achievement at test 1 were honest (4,2), care (4,5), and responsibility (4,4) with good category, students?social skills at test 1 were asked (4,6), contribute ideas (4,5), being a good listener (4,3), communication (4,4) and cooperation (4,0) with good category; students 'response to students' books, worksheets, learning media with value 4,07 was goodcategory.Based on the analysis of data analysis, it can be concluded that the development of the learning tool engine tune up Toyota referring to Problem based instruction Based onAuthentic can be effective, but it still need adjustment based on the situation and condition of the school.Key Words: Problem based instruction, Authentic, mastery learning.